Crowdfunding: An International Comparison and Analysis of the Constraints and Opportunities for Implementing it in Portugal - Nesme, Yoann (2016)
Crowdfunding, as we know it today, is a very recent activity that was born almost accidentally in the end of the 90’s decade. Due to the advent of the internet and the social networks, entrepreneurs are now able to promote their projects to a very large community. Whether it is composed by family, friends, acquaintances or simply people that are interested in the same topic or share the passion, the community is able to fund new ventures by individually investing modest amounts of money. In return, the entrepreneur can offer symbolic rewards, shares or other financial returns. New crowdfunding platforms are born almost every day all over the world, offering a new way of raising capital for their projects or a new way to invest their money in innovative ventures. Although crowdfunding is still finding its place in the financial services, successful cases such as Kickstarter demonstrate the power of the crowd in boosting creativity and productivity, financing thousands of projects by raising millions of dollars from thousands of investors. Due to regulatory restrictions, the most prominent model for now is reward-based crowdfunding, where the investors are prized with symbolic returns or privileged access to the products or services offered by the entrepreneurs. Other models such as peer-to-peer lending are also surging, allowing borrowers access to capital at a lower cost compared to so-called traditional financial institutions, and offering lenders a higher rate of return. But when it comes to offering shares to investors, i.e. using equity-based crowdfunding, entrepreneurs face regulatory obstacles in almost every country, where legislation was passed decades ago with the objective of promoting financially-capable ventures and protecting investors. Access to capital has become more difficult after the global economic recession of 2008, and for most countries it will not get easier in the near future, leaving start-ups and small enterprises with few options to start or expand their operations. In this study we attempt to answer the following research questions: how has equity-based crowdfunding evolved since its creation? Where and how has equity-based crowdfunding been implemented so far? What are the constraints and opportunities for implementing equity-crowdfunding in the world, and more particularly in Portugal? Finally, we will discuss the risks of crowdfunding and reflect on the future of this industry.